Dinosaurs decoded [videorecording (DVD)] - Levitt, Daniel; Carroll, Michael. (Associate professor of literature); Horner, John R. (Vivendi Entertainment, 2010)
Paleontologist Jack Horner and colleagues are challenging the long held belief that young dinosaurs looked like miniature versions of their parents. The transformations from childhood to adulthood may have been so dramatic that up to a third of all dinosaur species may vanish, leaving in their place a developing understanding of the complexity of dinosaur lives and the possible purpose behind features like horns lumps, bumps, and dome-heads.